Reading Philemon with Onesimus in the postcolony: exploring a postcolonial runaway slave hypothesis - Obusitswe Tiroyabone (Acta Theologica)
For centuries, the Philemon narrative has been read as the story of a slave that ran away from his master and must now be reconciled to him, and continue their master-slave relationship. Reading the narrative through a postcolonial lens yields another form of interpretation: reading the text with the signified and not the signifiers, reading with the oppressed and not the oppressor, and reading with the marginalised and not the centre. This article argues that the letter of Philemon and indeed the narrative of slavery must be decolonised. Using the Philemon narrative, this article proposes a postcolonial runaway slave hypothesis that shifts from John Chrysostom’s interpretation and those of many others after him significantly. The article argues that Onesimus was an intelligent person albeit a slave who sought to liberate himself using the very same system that oppressed him.